Formation of the Electric Field Distribution in Thin Electro-Optic Layers for Precision Correction their Optical Characteristics - R.N. Zhukov; S.V. Ksenich; I.V. Kubasov; A.A. Temirov; N.G. Timushkin; D.A. Kiselev; A.S. Bykov; M.D. Malinkovich; Yu.N. Parkhomenko (Журнал нано- та електронної фізики)
A method of making given field distribution within thin electro-optical layers by using narrow band electrodes placed at the same electric potential. A formula for electric field intensity produced by a single band electrode is obtained. Electric field modeling for different band electrode configurations is undertaken. It was shown, by applying piezoresponse force microscopy, that in case of highly inhomogeneous field the polarization of lithium niobate electro-optical film persisted only in the area above the band electrode.